MULTICULTURAL EDUCATION ENGLISH TEACHERS’ PERCEPTIONS AND PRACTICES IN INTERNATIONAL SCHOOL - Ni Putu Dian Utami Dewi; I G.A. Pt Novita Sari Paragae; Kadek Wiramarta; I Gusti Ngurah Aan Darmawan (Universitas Pendidikan Ganesha, 2023)
Multicultural education has been called to be important to develop students’ tolerance to be able to live together in a society which consists of various people. However, there is a lack of research conducted about how it is implemented in teaching certain subjects in the classroom. This research was aimed to find out English teachers’ perception on multicultural education, and its implementation both at school level and in the teaching and learning process in English Subject in one international school in Bali. The research was conducted in the form of a qualitative approach, especially case study design. The data were collected by administering questionnaires with open ended questions and followed by conducting interviews with 5 teachers as respondents. The data were then analyzed qualitatively. The result of the research found that multicultural education is considered important by teachers to be implemented in an international school, with language as the most important cultural element. It is also found that the practices of multicultural